Color Doppler imaging of a temporal artery – a new diagnostic tool in giant cell arteritis - Wietrzykowska, Claudia; Wiącek, Marta; Krytkowska, Elżbieta; Milchert, Marcin; Brzosko, Marek; Machalińska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Giant cell arteritis (GCA) is the most common potentially sight-threatening vasculitis. The typical clinical image with headache or jaw claudication accompanied by erythrocyte sedimentation rate (ESR) over 50 mm/h, confirmed by inflammatory features in temporal artery biopsy (TAB), is essential for GCA diagnosis. About 30% of patients experience a sudden loss of vision in one eye. Delay in treatment may lead to bilateral blindness, which makes GCA an ophthalmological emergency. An 80-year-old male patient was admitted to the ophthalmological emergency due to sudden and permanent vision loss of his left eye. He also complained of recurrent compressive headaches. However, he denied a history of general weakness, or jaw claudication. The distance visual acuity in the left eye had decreased to 0.1 and a blurred, elevated left optic disc in indirect ophthalmoscopy was observed. In palpation the temporal artery pulse was detectable. Interestingly, vascular smooth muscle thickening was detected in TAB. Despite the uncharacteristic TAB result and ESR equal to 27 mm/h, temporal artery color Doppler imaging (CDI) revealed the “halo” symptom confirmed by the pressure sign. According to typical features in CDI, GCA was diagnosed and the proper treatment was implemented. As a result, substantial resolution of inflammatory parameters in blood tests and CDI was observed. During the 24-month follow-up the good general and ophthalmological condition was maintained. Despite the lack of typical symptoms in the presented case, CDI determined quick and accurate diagnosis for proper treatment implementation. Color Doppler imaging is a non-invasive and highly specific tool for both diagnostics and treatment monitoring in GCA.